A study on visual dependency in hearing impaired children for perception of speech - Shruthi M N; Nagaraja M N (Journal of All India Institute of Speech and Hearing, 2013)
Visual speech perception is also known as lip reading and speech-reading. Visual speech is used by hearing impaired individuals, as well as individuals with normal hearing. The dependency of auditory performance on visual cues can be accounted to the concept of sensory integration. The aims of the study are : To assess the performance of children with hearing impairment in visual only and combined audiovisual tasks and to derive the implications of visual dependency in auditory performance based on their respective age and gender and also complexity of speech stimuli(words and sentences). Method included two groups of severe to profound sensorineural hearing impaired subjects. Each Group consists of 25 hearing impaired individuals. The stimuli were divided into visual (lip-read), auditory and picture stimuli presented in three conditions auditory only, audio and visual and audio-visual accompanied with the picture. The total combined Mean scores for words and sentences were slightly higher for the audiovisual with picture presentation when compared with the visual only presentation. Standard deviation scores of audio visual with picture presentation is lesser than visual only condition. Overall condition which was associated with picture presentation was more likely to receive higher scores than visual alone condition.